2017
DOI: 10.1007/s00106-017-0346-8
|View full text |Cite
|
Sign up to set email alerts
|

Eustachian tuboplasty and shrinkage of ostial mucosa with new devices

Abstract: The combined surgical procedure of balloon tubodilation with simultaneous QMR-mediated shrinkage of the tubal ostial mucosa and reduction of the posterior portion of the inferior turbinate was found to be an effective, safe, and complete treatment for tubal dysfunction in the majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This means that more severe AR or a greater degree of nasal obstruction is more likely to cause ETD. Many patients with severe AR are prone to concomitant inferior turbinate hypertrophy [ 24 ] and torus tubarius swelling, causing both nasal obstruction and ETD [ 25 ]. Previous studies have shown that patients with nasal obstruction due to inferior turbinate enlargement or nasal septum deviation have significantly higher ETDQ-7 scores than healthy controls [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This means that more severe AR or a greater degree of nasal obstruction is more likely to cause ETD. Many patients with severe AR are prone to concomitant inferior turbinate hypertrophy [ 24 ] and torus tubarius swelling, causing both nasal obstruction and ETD [ 25 ]. Previous studies have shown that patients with nasal obstruction due to inferior turbinate enlargement or nasal septum deviation have significantly higher ETDQ-7 scores than healthy controls [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of treatment for, or prophylaxis against, refractory CSF rhinorrhea via the ET, we envision an endonasal or lateral approach through the ET with introduction of a 14-gauge or 16-gauge semirigid microcatheter with flexible guidewire to cannulate and then obliterate the lumen from within; techniques for endonasal catheter delivery may build off of similar approaches to dilate the membranocartilaginous segment, such as described by Di Rienzo Businco et al 23 Such techniques would be useful for both otolaryngologists and neurosurgeons involved in lateral skull-based procedures involving the middle ear, as these practitioners already perform prophylactic middle ear and ET packing as components of these procedures. ET packing in this setting typically involves only obstruction of the tympanic orifice of the ET and destroys structures critical to hearing in the process.…”
Section: Discussionmentioning
confidence: 99%
“…Eustachian tube dysfunction in cases of localized amyloidosis may be treated by balloon Eustachian tube dilation; however, it may lead to unsatisfactory results in our cases. Further surgical approaches in literature include Quantum Molecular Resonance mediated shrinkage of the mucosa of the torus tubarius [18], laser tuboplasty [19] and a microdebrider [20]. Contributing factors, such as gastroesophageal reflux with signs of mucosal inflammation, should be addressed.…”
Section: Case Report Discussionmentioning
confidence: 99%